Analisa Komunikasi Persuasif Guru Menangani Siswa dengan Perilaku Menyimpang di SMK Karya - Mety Titin Herawaty (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Based on data from the Counseling Guidance teacher at the Karya Education Foundation Vocational High School (SMK) in the odd semester of the 2023/2024 academic year, there were 25 cases of student deviant behavior, which included bullying, violation of discipline, tardiness, and physical violence, this number shows an increase of 25% compared to the previous semester. Teachers as educators have an important role in guiding students towards more positive behavior. This study aims to analyze the role of persuasive communication teachers carry in dealing with students with deviant behavior at SMK Yayasan Pendidikan Karya. This research uses a qualitative approach with data collection techniques in the form of in-depth interviews with Counseling Guidance (BK) teachers, homeroom teachers, and several students, observation of interactions inside and outside the classroom, and documentation analysis in the form of student evaluation records. The results showed that persuasive communication of counseling guidance teachers, and homeroom teachers, which was carried out through an empathic approach, the use of polite language, as well as providing motivation and advice, was able to have a positive impact on changes in student behavior. A personal approach carried out consistently and tailored to the character of each student has proven to be more effective in building constructive relationships between teachers and students.